Strain improvement of Sporosarcina pasteurii for enhanced urease and calcite production - Achal, V.; Mukherjee, Abhijit; Basu, P.; Reddy, M. (Han'gug Mi'saengmul Saengmyeong Gong Haghoe, 2009)
Phenotypic mutants of Sporosarcina pasteurii (previously known as Bacillus pasteurii) (MTCC 1761) were developed by UV irradiation to test their ability to enhance urease activity and calcite production. Among the mutants, Bp M-3 was found to be more efficient compared to other mutants and wild-type strain. It produced the highest urease activity and calcite production compared to other isolates. The production of extracellular polymeric substances and biofilm was also higher in this mutant than other isolates. Microbial sand plugging results showed the highest calcite precipitation by Bp M-3 mutant. Scanning electron micrography, energy-dispersive X-ray and X-ray diffraction analyses evidenced the direct involvement of bacteria in CaCO 3 precipitation. This study suggests that calcite production by the mutant through biomineralization processes is highly effective and may provide a useful strategy as a sealing agent for filling the gaps or cracks and fissures in any construction structures.